Short-term therapeutic efficacy analysis of drug-coated balloon combined with chocolate balloon for the treatment of femoropopliteal artery lesions - Zhang, Rong; Jiang, Chao Yun; Cai, Tian Hong; He, Jiang Feng; Chen, Kai; Zhan, Teng Hui (Frontiers in Surgery, 2025)
BackgroundTo report our experience of short-term results of drug-coated balloon (DCB) combined with chocolate balloon in the treatment of femoropopliteal artery lesions.MethodsFrom June 2021 to December 2022, patients with femoropopliteal artery lesions (Rutherford classification 2–6) who underwent DCB combined with Chocolate PTA balloon catheter treatment were included. Clinical data of the patients were collected, and follow-up was conducted at 3, 6, and 12 months. The primary patency rate and the freedom from clinically-driven target lesion revascularization (f-TLR) rate were calculated by Kaplan–Meier survival curves.ResultsThis study included a total of 43 patients (mean age 72.84 ± 10.19 years, male proportion 67.4%) with 47 lesions. Among them, 17 lesions (36.2%) presented severe stenosis with an average lesion length of 110.41 ± 47.67 mm. Thirty lesions (63.8%) were identified as chronic total occlusions (CTO), with an average occlusion length of 104.13 ± 61.12 mm. The Kaplan–Meier survival curve estimated a primary patency rate of 87.2% at 6 months and 78.7% at 12 months. The f-TLR rate at 12 months was 85.1%, estimated by Kaplan–Meier survival curve. The mean ankle-brachial index (ABI) increased from 0.53 ± 0.12 before the surgery to 0.87 ± 0.12 at 12 months postoperatively, and this difference was statistically significant (p < 0.001). A total of 91.5% of patients (43/47) showed a decrease in Rutherford classification at 12 months postoperatively. The proportion of patients with Rutherford class 4–6 decreased from 70.2% (33/47) preoperatively to 4.3% (2/47) at 12 months postoperatively, and this difference was statistically significant (p < 0.001). Among the limbs, 34 (72.3%) experienced dissection during the surgery, with 29 cases classified as type B or lower dissection and 5 cases classified as type C or higher (severe dissection) (10.6%). Two limbs (4.3%) required the use of salvage stents. There were no procedure- or device-related deaths within the 12-month period. Twelve limbs (25.5%) underwent minor amputations (toe amputations).ConclusionThe combination of DCB and chocolate balloon angioplasty has achieved satisfactory patency rates and f-TLR results in 1-year follow-up for the treatment of femoropopliteal artery lesions. However, further confirmation of these findings is needed through multicenter data and long-term follow-up results.